Sources and pathways of halomethoxybenzenes in northern Baltic estuaries - Bidleman, Terry; Agosta, Kathleen; Andersson, Agneta; Brugel, Sonia; Ericson, Lars; Hansson, Katarina; Nygren, Olle; Tysklind, Mats (Frontiers in Marine Science, 2023)
Introduction Thousands of halogenated natural products (HNPs) are generated in the ocean and on land. A subset of these, halomethoxybenzenes (HMBs), are released from both natural and anthropogenic sources. Here we consider: 1. Brominated anisoles (BAs), transformation products of bromophenols. 2. Drosophilin A methyl ether (DAME: 1,2,4,5-tetrachloro-3,6-dimethoxybenzene), a secondary metabolite of terrestrial fungi. 3. Tetrachloroveratrole (TeCV: 1,2,3,4-tetrachloro-5,6-dimethoxybenzene), a lignin byproduct found in bleached kraft mill effluent. 4. Pentachloroanisole (PeCA), a metabolite of the wood preservative pentachlorophenol. Methods We examined several ecosystem compartments to determine sources and exchange processes for these HMBs: air, precipitation, rivers, forest fungi and litter, and water from northern Baltic estuaries and offshore. Samples were analyzed for HMBs by capillary gas chromatography – quadrupole mass spectrometry. Results and discussion All four types of HMBs were found in air, and BAs, DAME and TeCV were also present in precipitation. BAs and DAME were common in rivers and estuaries, whereas TeCV was low and PeCA was below detection. DAME was identified in several species of fungi and in forest litter; TeCV was occasionally present, but BAs and PeCA were below detection. Concentrations of BAs were higher in estuaries than in rivers or offshore waters, showing that estuaries are hot spots for production. BAs were negatively or not correlated with chlorophyll-a, suggesting contribution by heterotrophic bacteria as well as known production by phytoplankton and macroalgae. DAME was negatively or not correlated with BAs and did not appear to be produced in the estuaries; fungi and forest litter containing fungal mycelia are suggested as sources. HMBs volatilize from sea and land, disperse through the atmosphere, and return via precipitation and rivers. Production and biogeochemical cycles are influenced by climate change and we suggest BAs and DAME for following partitioning and exchange processes.